Development of Ethnoscience-Oriented Multimedia Learning Process of Salt Making on Conductivity Materials on the Response of Junior High School Students - Dewi Suryani; Mochammad Yasir; Rahmad Fajar Sidik (Journal of Science and Science Education, 2022)
Chemistry learning at the junior high school level has not discussed in depth the material presented. Students tend to like science learning without formulas or calculations which make it difficult for students to understand chemistry. The solution that can be given is to develop learning media in the form of multimedia learning based on salt ethnoscience on conductivity material. The purpose of this study was to obtain an ethnoscience study of conductivity material and to find out students' responses to the media. This research uses a descriptive qualitative method with ADDIE development model. The research location is in one of the salt ponds in Bangkalan Regency and in SMP Negeri 2 Kamal. The sampling method was simple random sampling as many as 10 students of class VII. Data collection techniques using interviews, questionnaires, and documentation. The percentage of student responses on the display aspect is 97.33% and the material aspect is 94.25% which is included in the very positive criteria